Perspectives on colorectal cancer screening in a multiethnic population in Kuala Lumpur using the health belief model: a qualitative study - Nur Suhada Ramli,; Azmawati Mohammed Nawi,; Mohd Rohaizat Hassan,; Faiz Daud,; Noor Azimah Muhammad,; Wong, Zhiqin (Universiti Kebangsaan Malaysia, 2025)
Colorectal cancer (CRC) carries a significant burden in most world regions. However, its screening uptake remains low. This study aimed to explore awareness and perspectives on CRC screening program in a multiethnic population and their preference for CRC screening decision aid. In-depth interviews were conducted until data saturation was reached. All interviews were audiotaped, transcribed verbatim, translated to English and analysed thematically using hybrid inductive and deductive approaches. 17 informants from three main ethnic groups (Malay, Chinese and Indian) with various levels of risk for developing CRC were recruited. Awareness on CRC screening program was found to be low. Majority of informants never heard of CRC screening program. Among 11 eligible informants, only five experienced CRC screening uptake. Thematic analysis of the transcripts yielded six major themes; knowledge on CRC, screening process, authority’s role, curability, willingness to screening and preference for decision aid, and they were mapped onto the Health Belief Model. Specific multiethnic perspectives found included preference for traditional medicine coming from all ethnics, and reliance in God coming from Malay informants. Majority preferred short videos as CRC screening decision aid, in the form of animation and live-action screenplay. Exploration of perspective of CRC screening helps in producing impactful decision aids. Future efforts should focus on developing short videos that incorporate population’s perspectives and can be disseminated through electronic media.